KINERJA PEGAWAI PEMERINTAH KECAMATAN BUNAKEN KEPULAUAN KOTA MANADO - SANDUYO, ADRIAN; OGOTAN, MARTHA; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2017)
Abstract: This study moved from a general phenomenon is still not optimal performance of some employees in governmentagencies such as district government. The purpose of this research is to know and describe the performance of employeesin Bunaken Kepulauan sub-district of Manado City. The concept used is four dimensions of employee performance ofFlippo namely the quantity of work, quality of work, toughness, and attitude. This research uses a qualitative method. Theresearch informant is the sub-district head and seven PNS of the Bunaken Kepulauan sub-district office. Data collectionusing interview guidelines, while the analytical technique used is interactive model analysis of Miles and Hubernan. Basedon the results of data analysis concluded that the performance of the employees in Bunaken Kepulauan district is generalhas not been optimal but it shows the quality of work is good enough seen from the four dimensions of performance used:(1) The quantity of employees work is generally seen from the ability to execute and complete the task/work routine orregular, and the speed of completion of extra and urgent tasks. (2) The quality of employees work is generally good seenfrom the accuracy of work, work accuracy, job completeness, and tidiness work generated employees. (3) The employeestoughness is generally good seen from the toughness following the command of official, initiative, attendance orabsenteeism, and timeliness of completion of job duties. (4) The attitudes of employees generally good/positive views ofemployees attitudes toward changes and increasing the number of job duties, attitudes toward fellow colleagues and attitudestowards cooperation It is recommended that the performance of the employees in bunaken kepulauan sub-district still needto be improved by taking measures such as: providing adequate means and equipment such as computers and devices andthe creation of a work environment that encourages employees enthusiasm and passion; improve employees knowledge andskills through education and technical training that are directly related to their field of duty; and the development oftoughness through disciplined coaching and attitude as well as trainingKeywords : The Performance, Employess, Sub-district Government